2005
DOI: 10.1602/neurorx.2.3.447
|View full text |Cite
|
Sign up to set email alerts
|

The use of the R6 transgenic mouse models of Huntington’s disease in attempts to develop novel therapeutic strategies

Abstract: Summary:Huntington's disease (HD) is a genetic neurodegenerative disorder. Since identification of the disease-causing gene in 1993, a number of genetically modified animal models of HD have been generated. The first transgenic mouse models, R6/1 and R6/2 lines, were established 8 years ago. The R6/2 mice have been the best characterized and the most widely used model to study pathogenesis of HD and therapeutic interventions. In the present review, we especially focus on the characteristics of R6 transgenic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(140 citation statements)
references
References 170 publications
5
132
0
3
Order By: Relevance
“…Strain R6/2 is the product of strong expression of a transgene containing human mHTT exon 1 and its promoter (21). It has been widely used in the assessment of potential therapeutic interventions for HD (22,23). We found that D2GFP expression in the MSNs of R6/2 showed significant differences from the values for wild-type littermates at the earliest age we evaluated, 4.5-5 wk of age.…”
Section: D2gfp Loss Is Progressive In Both Fragment and Full-length Hdmentioning
confidence: 85%
“…Strain R6/2 is the product of strong expression of a transgene containing human mHTT exon 1 and its promoter (21). It has been widely used in the assessment of potential therapeutic interventions for HD (22,23). We found that D2GFP expression in the MSNs of R6/2 showed significant differences from the values for wild-type littermates at the earliest age we evaluated, 4.5-5 wk of age.…”
Section: D2gfp Loss Is Progressive In Both Fragment and Full-length Hdmentioning
confidence: 85%
“…1A, HDAC1 expression is elevated in the striatum of R6/2 mice, but not in extra-striatal tissues, which are relatively unaffected by neuropathology. It is known that neuropathology and behavioral deficits in R6/2 mice are not obvious at 6 weeks, but clearly discernible at 10 weeks of age (25). As shown in Fig.…”
Section: Hdac1 Promotesmentioning
confidence: 87%
“…R6/2 mice are transgenic for the first exon of the human huntingtin gene carrying about 120 CAG repeats. These mice exhibit a progressive neurological phenotype that mimics many features of human HD including selective striatal neuropathology, intracellular aggregates, reduced motor performance, and shortened lifespan (25). As shown in Fig.…”
Section: Hdac1 Promotesmentioning
confidence: 95%
“…R6/2 mice express a 144 CAG repeat expansion within the first exon of the huntingtin gene, which yields a relatively severe disease phenotype. Untreated R6/2 mice develop rapidly progressive neurological impairment, and typically die between 13 and 15 weeks of age [140,141]. As in the rat, AdBDNF and AdNoggin treatment induced significant neuronal recruitment in both R6/2 mice and their wild-type controls [98].…”
Section: Induced Neuronal Addition As a Treatment For Huntington's DImentioning
confidence: 99%